Convention Delegate Study of 1972: Women in Politics - Miller, Warren E. ([Verlag nicht ermittelbar], 1984)
This study consists of two analytically distinct parts. The first 351 variables contain information from 2,587 delegates to the Republican and Democratic national nominating conventions of 1972 who responded to a pre-convention mail questionnaire (response rate of 58 percent). Data for the next 381 variables were gathered in post-convention personal interviews with 1,336 respondents selected as a representative sample of delegates. Either segment of the data may be analyzed independently, or the appropriate subset of merged data may be selected. The study focused on the changing role of women in politics, utilizing the nominating conventions as a means of defining and identifying an elite segment of the population and women in politics at one point in time. The mail questionnaire provided information on the nature and composition of each of the national conventions in terms of the delegates' personal life histories, political expectations and aspirations, and attitudes towards candidates, issues, and groups in society and at the conventions. The personal interview built on the pre-convention instrument and examined in depth the candidate selection process, the convention proceedings, and the psychological factors involved in women's political activity. Demographic data include age, sex, race, place of birth, marital status, number of children, ethnicity, education, parents' and spouse's levels of education, occupation, and family income.